HLA allele frequencies and susceptibility to COVID‐19 in a group of 99 Italian patients. (3rd September 2020) - Novelli, Antonio; Andreani, Marco; Biancolella, Michela; Liberatoscioli, Laura; Passarelli, Chiara; Colona, Vito Luigi; Rogliani, Paola; Leonardis, Francesca; Campana, Andrea; Carsetti, Rita; Andreoni, Massimo; Bernardini, Sergio; et al.
Abstract : With the aim to individuate alleles that may reflect a higher susceptibility to the disease, in the present study we analyzed the HLA allele frequency distribution in a group of 99 Italian patients affected by a severe or extremely severe form of COVID‐19. After the application of Bonferroni's correction for multiple tests, a significant association was found for HLA‐DRB1*15:01, ‐ DQB1*06:02 and ‐B*27:07, after comparing the results to a reference group of 1017 Italian individuals, previously typed in our laboratory. The increased frequencies observed may contribute to identify potential markers of susceptibility to the disease, although controversial results on the role of single HLA alleles in COVID‐19 patients have been recently reported.